Factors Causing Pending Claims in BPJS Participant Patients at Imelda Worker General Hospital Indonesia Medan Year 2022 - Mei Sryendang Sitorus; Puput Melati Hasibuan; Erlindai Erlindai; Johana Christy; Joel Roganda Manik (Jurnal EduHealth, 2023)
BPJS Health claims are the submission of hospital patient care costs by the hospital to the BPJS Health party which is carried out collectively and billed by the hospital to the BPJS Health every month. Based on an initial survey conducted at the Indonesian Workers' Imelda RSU, it was one that caused the pending claim file (unclaimed), namely the incompleteness of recording Medical Records. As for the pending claim (unclaimed) it is found more in hospitalizations, and based on information that researchers found it is known that the number of inpatients at Indonesian Workers' Hospital in 2021 had 8,004 patients. Inpatient file data submitted in the last month, April 2022, was 472 files. A total of 371 files (78.6%) were successfully claimed, 100 files (21.2%) were pending claims, and 1 file (0.2%) which failed purif. The method used in this study is quantitative descriptive with a cross section approach, and by univariate data analysis. Research results show factors that cause pending claims in BPJS participant patients in Indonesian Workers' Hospital are coding mismatches there are as many as 25 medical records (50%), incompleteness of administrative data of 10 medical records (20%), and incompleteness and or inaccuracy in filling medical records of 15 medical records (30%). Suggestions put forward are making regulations in the form of policies, rules, or SOPs, as well as adding training and attending seminars related to coding and enforcement of diagnoses.